Desenvolvimento de formulações de Bacillus subtilis para controle da podridão floral em citros - Klein, Mariana Nadjara (2012)
Brazil is the world's largest producer of orange, seated in an area of 839.000 hectares, of which 77% are located in the southeast. Despite the importance of this crop, the citrus industry faces serious problems represented by fungal diseases that reduce productivity such as citrus post-bloom fruit drop (PDF), caused by Colletotrichum acutatum. As control is predominant spraying chemicals. Considering the financial costs, environmental damage and public health of these applications, it is necessary to study new control alternatives, and among these, the biological control. Therefore this study aimed to develop a formulation of Bacillus subtilis, based different transport vehicles, with or without additives, aiming to control the PDF. The results showed that the powder as a vehicle for transport, provided a greater viability of bacterial cells stored in the two temperatures tested (1 and 22 ° C) for a period of 12 months. In vitro tests showed that the powder plus urea (0.02%) inhibited both the mycelial growth, as the germination of C. acutatum. The additives urea (0.02%) and ammonium molybdate (1mM) optimized the formulation, when tested in the same flower deployed. Control data under field conditions, showed that B. subtilis in powder plus urea (0.02%) yielded 72.7% of flowers without infection by the pathogen and 56.4% of the average number of effective fruits (ANEF) and on the other hand, the control treatment was obtained 8.8% flowers and 0.83% of healthy ANEF, chemical treatment (thiophanate-methyl) showed 69.6% of healthy flowers and 46.7% ANEF. It is concluded that, based formulation B. subtilis, with talc as a transport vehicle, plus an additive (urea 0.02%) kept the viability of bacteria cells and was effective in the controlling of disease.